2018
DOI: 10.1016/j.jiec.2017.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of oxidants as a biocide for biofouling control in industrial seawater cooling towers

Abstract: Industrial and Engineering Chemistry. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(22 reference statements)
0
14
0
Order By: Relevance
“…In comparison, QQ enzymes that degrade extracellular QS signals are viewed as imposing less of a burden on cellular metabolism (Fetzner, 2015), and hence, they minimize the development of resistance toward these greener inhibitory agents. In most instances, QQ enzymes or bacteria with enzymatic activity from marine sources (Huang et al, 2012; Mayer et al, 2015; Tang et al, 2015; Liu et al, 2017; Rehman and Leiknes, 2018) were demonstrated for their efficiencies to quench QS in only minimal or nutrient medium, which deviate significantly from conditions in marine industrial systems such as seawater desalination plants (salinity: 46,400 ppm, temperature: 22–33°C, and pH 8.1–8.3) (Khawaji et al, 2007) and cooling towers (e.g., salinity: >35,000 ppm, and temperature 32–48°C) (Al-Bloushi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, QQ enzymes that degrade extracellular QS signals are viewed as imposing less of a burden on cellular metabolism (Fetzner, 2015), and hence, they minimize the development of resistance toward these greener inhibitory agents. In most instances, QQ enzymes or bacteria with enzymatic activity from marine sources (Huang et al, 2012; Mayer et al, 2015; Tang et al, 2015; Liu et al, 2017; Rehman and Leiknes, 2018) were demonstrated for their efficiencies to quench QS in only minimal or nutrient medium, which deviate significantly from conditions in marine industrial systems such as seawater desalination plants (salinity: 46,400 ppm, temperature: 22–33°C, and pH 8.1–8.3) (Khawaji et al, 2007) and cooling towers (e.g., salinity: >35,000 ppm, and temperature 32–48°C) (Al-Bloushi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, seawater circulation cooling technology is currently attracting increased attention. In coastal areas, using seawater instead of freshwater as circulating cooling water (including in seawater cooling tower applications) can not only relieve the pressure of marine thermal pollution but could also be valuable in solving the freshwater shortage problem [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The standard biofouling control methods consist of dosage of biocides such as sodium hypochlorite, chlorine dioxide or bromine in the cooling systems (Al-Bloushi et al 2018;Pinel et al 2020). Although, these chemicals considerably slow down the build-up of biofilms by deactivating planktonic bacterial cells, they cannot completely prevent biofilm formation and have little curative action.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, most CTs are operated with freshwater (e.g. ground or surface water), causing less damage to the process than seawater, which is frequently used, for example, in the Middle-East (Al-Bloushi et al 2018). In this study, seawater reverse osmosis (SWRO) permeate was selected as a reference feed water for three parallel pilot-scale CTs due to its ultra-low content of the elements and nutrients required for microbial growth: RO permeate water has one of the highest water qualities achievable.…”
Section: Introductionmentioning
confidence: 99%